2015
DOI: 10.2224/sbp.2015.43.5.855
|View full text |Cite
|
Sign up to set email alerts
|

Face Attractiveness in Building Trust: Evidence from Measurement of Implicit and Explicit Responses

Abstract: We explored individuals' behavior in relation to level of trust when they encounter attractive or unattractive faces. Individuals' implicit responses were examined in Experiment 1 and their explicit responses in Experiment 2. Results of Experiment 1 indicated that the latency of the unattractive faces with words indicating trust or attractive faces with words indicating distrust (incompatible group) was twice as long as that of the attractive faces with trust words or unattractive faces with distrust words (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
6
23
0
Order By: Relevance
“…We found that raters transferred more money to the odour donors if they found their body odour pleasant. This parallels studies demonstrating a relationship between a man's attractiveness and his apparent trustworthiness 29 . An explanation for why good-looking men are trusted more than men who are less good-looking is that attractiveness serves as an easily accessible cue to more complex and not easily accessible traits such as trustworthiness 36 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…We found that raters transferred more money to the odour donors if they found their body odour pleasant. This parallels studies demonstrating a relationship between a man's attractiveness and his apparent trustworthiness 29 . An explanation for why good-looking men are trusted more than men who are less good-looking is that attractiveness serves as an easily accessible cue to more complex and not easily accessible traits such as trustworthiness 36 .…”
Section: Discussionsupporting
confidence: 78%
“…For example, Wilson and Eckel 28 showed that good-looking trustees were viewed as more trustworthy in a game involving trust and reciprocity. A similar "beauty premium" was found in a hypothetical trust game, where participants invested significantly more money in good-looking partners than they did in partners that were less good looking 29 . An evolutionary account of this "beauty premium" states that attractiveness benefits can be explained by mating motivations 30 .…”
Section: Identifying Trustworthy Partners Is An Important Adaptive Chsupporting
confidence: 53%
See 1 more Smart Citation
“…This may be a result of the degree of facial unattractiveness. In the pilot study, the female face assigned to the matched unattractive target was ranked as less unattractive than the faces assigned to the mismatched targets with unattractive faces, which would remain consistent with Zhao et al (2015). Other research found that same-sex friends normally have the same level of physical attractiveness (Bleske-Recheck & Lighthall, 2010), so participants in the present study might have indicated a preference to be friends with someone who they considered to be of similar attractiveness as themselves.…”
Section: Discussionmentioning
confidence: 57%
“…We analyze whether trustworthiness can be correctly predicted based on facial appearance by asking a second group of subjects to evaluate the expected trustworthiness of the participants of the Trust Game. Some prior studies used photos of players in the Trust Game, but these studies differ from our approach as they show pictures of the player to their counterpart, thus giving the player more information (see for example Wilson & Eckel, 2006;Buchan et al, 2008;Centorrino et al, 2014;Zhao et al, 2015). 2 There exists also research on the influence of other information on the observed behavior in the Trust Game and in other games.…”
Section: Introductionmentioning
confidence: 99%